If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2x = 6x + -2 Combine like terms: 5x + 2x = 7x 7x = 6x + -2 Reorder the terms: 7x = -2 + 6x Solving 7x = -2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7x + -6x = -2 + 6x + -6x Combine like terms: 7x + -6x = 1x 1x = -2 + 6x + -6x Combine like terms: 6x + -6x = 0 1x = -2 + 0 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 5x-6(3x+4)=9(x-6)+3 | | -9x+4x+15-10x= | | 7u^2-48u-7=0 | | 0.02-0.02(x+2)=-0.04(2-x) | | 6x+6=4x+2 | | 4-(3.5x+2)=x-7 | | 10y-7-6y+9= | | 125x^3-8= | | -10y-7-6y+9= | | 5[15x+25]=950 | | 3x^2-4x-9=0 | | 3x^5-6x^3+11x^2-10=0 | | x+x+9=95 | | 3(x-2)+x+4=2(x-1) | | 2(1-11n)+11=-8(n+1)-7 | | -4x+7=27 | | -2a+40+9a=4a-7a | | x^2*5y^4= | | 4(3y+-1)+13=5y+2 | | 6b=6 | | x^2*5y^2= | | 7[200]+12x=1736 | | 2.5x+2=4x+5 | | 4(3y-10)+13=5y+2 | | x^3-8x-6=0 | | 15x-4=2x+9 | | x+10=x | | 4ax^4-22ax^2+10a= | | 2x+5+7x=32 | | -5x+x+3=-13 | | 14=8x+2y | | -(3+4)=6z-3(3z+2) |